THINK PAIR SHARE WITH AUTHENTIC PICTURES IN READING COMPREHENSION CLASS - Ni Nengah Dwi Antari; Dewa Ayu Ari Wiryadi Joni; Ni Wayan Krismayani (Academic Journal on English Studies (AJOES), 2023)
This study was done based on the result of the observation and pre-test which showed that most of the students in SMP Negeri 3 Sukawati faced problem in reading comprehension. The students had difficulty in identifying general information, specific information, textual meaning and textual reference of the text. The researcher engaged 38 students in two cycles of classroom action research. The pre-test, post-test, and questionnaire were the research tools. By comparing the outcomes of the pre-test and post-test, the data were examined. The outcome revealed that the subjects' reading comprehension scores were rising. A questionnaire that was sent out at the conclusion of the previous cycle as further evidence revealed favorable answers to the application of the think-pair-share technique with an image. Pre-test scores were 52.10, post-test scores were 65.07, and post-test scores were 80.07. It is possible to draw the conclusion that the think-pair-share method can enhance the reading comprehension of SMP Negeri 3 Sukawati eighth graders in the academic year 2022/2023. This study provided empirical evidences of how think pair share with authentic pictures could be used in teaching reading comprehension.